Corporate Governance Country Assessment : Togo - World Bank (Washington, DC, 2014)
The purpose of this ROSC assessment of corporate governance in Togo is to help improve corporate governance in the country by assessing law and practice, suggesting reforms, and supporting the country in its effort to implement changes for better corporate governance. Corporate governance refers to the structures and processes for the direction and control of companies. Corporate governance concerns the relationships among the management, board of directors, controlling shareholders, minority shareholders and other stakeholders. This definition focuses on company performance and shareholder value. For emerging market countries, improving corporate governance can serve a number of important public policy objectives. Good corporate governance reduces emerging market vulnerability to financial crises, reinforces property rights, reduces transaction costs and the cost of capital, and leads to capital market development. Weak corporate governance frameworks reduce investor confidence, and can discourage outside investment. In state-owned enterprises (SOEs), good corporate governance could improve performance and social service, and lessen impact on state budget. Due to the small market size for listed securities in Togo, the scope of the present report is broadened to include a corporate governance assessment of non-listed public limited companies, SOEs, as well as private and state-owned banks (SOBs).